Chemical Reaction and Uniform Heat Generation or Absorption Effects on MHD Stagnation-Point Flow of a Nanofluid over a Porous Sheet - Imran, Anwar; Abdul Rahman, Mohd Kasim; Zulkhibri, Ismail; Mohd Zuki, Salleh; Sharidan, Shafie (IDOSI Publication, 2013)
The objective of this work is to analyze the chemical reaction and heat generation or absorption effects on MHD stagnation-point flow of a nanofluid over a porous stretching sheet. The uniform magnetic field strength B is applied in the direction normal to the flow. A highly nonlinear problem of nanofluid is modeled for the modified Bernoulli's equation of an electrically conducting nanofluid by incorporating the effects of embedded flow parameters such as Brownian motion parameter, thermophoresis parameter, velocity ratio parameter, heat generation/absorption parameter, suction or injection parameter, chemical reaction parameter, Hartmann number, Prandtl number and Lewis number. A system of nonlinear partial differential equations is reduced to nonlinear ordinary differential equations and then solved using finite difference scheme known as the Keller-box method. A parametric study of the involved physical parameters is conducted and a set of numerical results is illustrated in graphical and tabular forms. A comparison with published results is also provided.